2013
DOI: 10.1002/chem.201300985
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design for Cooperative Recognition of Specific Nucleobases Using β‐Cyclodextrin‐Modified DNAs and Fluorescent Ligands on DNA and RNA Scaffolds

Abstract: We propose a binary fluorimetric method for DNA and RNA analysis by the combined use of two probes rationally designed to work cooperatively. One probe is an oligonucleotide (ODN) conjugate bearing a β-cyclodextrin (β-CyD). The other probe is a small reporter ligand, which comprises linked molecules of a nucleobase-specific heterocycle and an environment-sensitive fluorophore. The heterocycle of the reporter ligand recognizes a single nucleobase displayed in a gap on the target labeled with the conjugate and, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…The ratiometric signal was indeed effective, and the strategy would be sufficiently flexible for further design of this class of probes to detect all possible mutations. Also, since the naphthyridine (ATMND) moiety can bind to the other non-Watson-Crick base pairing sites in the DNA duplex as demonstrated in our previous work, [63][64][65][66][67][68][69][70][71][72] ATMND-DBD would have a potential for further applications such as gap site binding in a binary fluorometric method, 63,64 detecting mismatches in trinucleotide repeats, 65 and affinity-labeling in aptamer assays or molecular beacons.…”
Section: Dna-binding Small Ligand For Ratiometricmentioning
confidence: 99%
“…The ratiometric signal was indeed effective, and the strategy would be sufficiently flexible for further design of this class of probes to detect all possible mutations. Also, since the naphthyridine (ATMND) moiety can bind to the other non-Watson-Crick base pairing sites in the DNA duplex as demonstrated in our previous work, [63][64][65][66][67][68][69][70][71][72] ATMND-DBD would have a potential for further applications such as gap site binding in a binary fluorometric method, 63,64 detecting mismatches in trinucleotide repeats, 65 and affinity-labeling in aptamer assays or molecular beacons.…”
Section: Dna-binding Small Ligand For Ratiometricmentioning
confidence: 99%
“…The precise introduction of functional molecules into these scaffolds can provide unique DNA-based materials and interfaces such as luminescent molecular sensors, 1−5 conductive wires, 6−11 chiral selective catalysts, 12−15 and microenvironments for DNA-templated reactions. 16−19 For several years, we have been studying DNA-templated reactions such as metal complex formation, 20−22 photochemical reactions, 23−25 supramolecular inclusion complex formation, 26,27 and allosteric assembly of DNA conjugates. 28 In a series of studies, we found that luminescent lanthanide (Ln) complexes could be successfully formed by sequence-specific hybridization between a template and two DNA conjugates carrying ethylenediaminetetraacetic acid (EDTA) and 1,10phenanthroline (phen) as metal-capturing and sensitizer moieties, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…For several years, we have been studying DNA-templated reactions such as metal complex formation, photochemical reactions, supramolecular inclusion complex formation, , and allosteric assembly of DNA conjugates . In a series of studies, we found that luminescent lanthanide (Ln) complexes could be successfully formed by sequence-specific hybridization between a template and two DNA conjugates carrying ethylenediaminetetraacetic acid (EDTA) and 1,10-phenanthroline (phen) as metal-capturing and sensitizer moieties, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy is intriguingly straightforward, but its implementation into practice usually requires case-dependent presynthesis of the incorporators and subsequent challenging modification of DNA. Another universal and attractive strategy is introduction of local structures into DNA, such as an abasic site (AP site), a bulge site, ,, a gap site, , etc., which provide cavities ready for the exogenous probe binding. In these structures, only the target nucleotides are left unpaired to be recognized and the probe manipulation is more flexible since the covalent attachment of incorporators into DNA is unnecessarily required.…”
mentioning
confidence: 99%
“…In these structures, only the target nucleotides are left unpaired to be recognized and the probe manipulation is more flexible since the covalent attachment of incorporators into DNA is unnecessarily required. Upon entering into these sites, the signal probes report the type of SNP with changes in, for example, dielectric-environment-dependent fluorescence, self-folding-sensitive emission, and some photophysical behaviors, including excited-state intramolecular proton transfer (ESIPT), photoinduced electron transfer (PET), etc. …”
mentioning
confidence: 99%